Primary liver lymphoma: review of the literature and clinical case presentation - A. K. Smolyaninova; A. V. Gubkin; Ye. Ye. Zvonkov; Yu. A. Kucheryavy (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the case presentation. To demonstrate the rare case of extranodal lymphoma with primary extensive liver involvement which caused difficulties at diagnosis verification. Despite of rapid disease progression with development of severe liver failure, that resulted in poor prognosis, patient demonstrated significant response to high-dose chemotherapy and achieved long-term remission. Summary. Male 38-year-old patient developed acute symptoms: sweating, general weakness, febrile fever, weight loss (50 kg for 4 months), abdominal pain combined to hepatomegaly and multiple focal lesions in the liver according to abdominal US, with 5 unsuccessful attempts for 6 months to receive informative tissue sample. Laboratory tests revealed progressive signs of liver failure at normal level of alpha-fetoprotein and carcino-embryonic antigen; clinical signs included progressive manifestations of liver encephalopathy, skin hemorrhages, severe edema, ascites, pruritis and excoriations. Empirical therapy by prednisolon resulted in no responce and was complicated by development of steroid diabetes. The diagnosis of diffuse B-macrocellular lymphoma was established only via open liver biopsy. Four sessions of high-dose polychemotherapy according to mNHL-BFM-90 program resulted in rapid reduction of liver size, recovery of consciousness, resolution of encephalopathy signs, however the liver and the spleen remained enlarged with focal parenchimatous lesions that required laparoscopy with biopsy of the pathological foci, the latter revealed no remaining neoplastic cells. During 10 years of patient follow-up liver function remains compensated, focal lesions in the liver and the spleen are undetectable, that indicates achievement of 113-months complete tumor remission. Conclusion. Presence of multiple focal lesions in the liver and signs of progressive liver failure at normal level of tumor markers requires taking into account primary liver lymphoma in the spectrum of possible etiologies. Potentially poor life prognosis in similar clinical situations at detection of primary liver lymphoma can flip to favorable due to high efficacy of modern chemotherapeutic agents.